Development of E-Modules Containing Mutual Cooperation Characters on the Theme of Local Wisdom in Elementary Schools - Novi Eka Saputri; Saddam Fathurrachman; Mudayat Mudayat (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Character education, especially in the context of the Independent Curriculum and the Pancasila Student Profile (P5), is an important aspect in forming a competent and characterful generation. One of the core values that needs to be instilled is mutual cooperation, which reflects the spirit of cooperation and social solidarity in Indonesian culture. However, the integration of mutual cooperation values in learning in elementary schools faces challenges, especially related to the limited availability of effective teaching materials. This study aims to develop an e-module based on local wisdom that integrates mutual cooperation values. The main focus of this study is to assess the validity or feasibility of the e-module developed in supporting interactive and relevant project-based learning. The method used is Research and Development ( R&D) with the ADDIE model ( Analyze, Design, Development, Implementation, and Evaluation). Data collection in this study used a Likert scale . This study produced an e-module that integrates the value of mutual cooperation on the theme of local wisdom in Elementary Schools. Based on the evaluation conducted, this e-module shows good feasibility, in the assessment aspect of the module shows a level of interest of 94% and practicality of 89%, confirming that this module is relevant, interesting, and easy to use in character-based learning.